IMPROVING ORGANIZATIONAL COMMITMENT THROUGH TEAMWORK STRENGTHENING, ORGANIZATIONAL CULTURE AND JOB SATISFACTION: A PATH ANALYSIS AND SITOREM STUDY ON TEACHERS ENTITLED AS CIVIL SERVANT OF PUBLIC HIGH SCHOOLS IN DEPOK - Juliwardi Juliwardi; Prof. Dr.Ing. Soewarto Hardhienata; Dr. Eka Suhardi (JF Publisher, 2024)
The major issues related to organizational commitment are increasingly needed, especially on the organizational commitment of teachers in order to make the education quality better in this era of globalization. Improving the quality of teachers as the educators continues to be pursued, one of which is by developing organizational commitment to teachers. The purpose of this research is to identify strategies and optimal solutions to increase organizational commitment on teachers entitled as civil servant of public high schools in Depok by examining the influence of teamwork, organizational culture, as well as job satisfaction on organizational commitment. The selected sample in this research consist of 180 people with the Slovin formula. This research applies a method of survey and a path analysis approach, continued by SITOREM analysis. The findings of this research concluded that the strategy to increase organizational commitment in teachers entitled as civil servant of public high schools in Depok could be conducted through strengthening teamwork, organizational culture, and job satisfaction. The outcomes of the SITOREM analysis identified that there are several indicators on teachers characteristics that should be improved further.